ANALISIS KINERJA PEGAWAI DAN KUALITAS PELAYANAN KARTU TANDA PENDUDUK (KTP) DI KECAMATAN MANDONGA KOTA KENDARI - La Ode Abdul Harlan (Universitas Halu Oleo, 2019)
This research aims to (1) Analyze and find out how the performance of employees in Mandonga District in providing KTP services to the community, and (2) Analyze and find out how the quality of KTP services in Mandonga District.The method used in this research is descriptive qualitative. The results of this study indicate that the performance of the apparatus in the District of Mandonga in KTP services is quite good. This can be seen from the indicators of productivity, quality of service responsiveness, and responsibility, but there is still the behaviour of officials who are concerned with personal interests rather than the quality of the kites provided. In the variable quality of public services shows that in the Identity Card service there are still irregularities in the actions, attitudes or behaviour of the authorities, so that it causes a reaction from the public (social control) to the deviation of actions, attitudes and behaviour of government officials, including legal and illegal levies against Identity Card services. In line with the results of this study, in order to improve and even avoid the occurrence of deviations in the actions, attitudes and behaviour of the Mandonga District government officials, it is necessary to review the rules that are imposed regarding the procedures and costs of levies in KTP services